Identification of attitudes towards youth activity in the context of globalization - Shukhrat Mamatkulov (Proceedings of The ICECRS, 2019)
This article examines the problems arising in the process of globalization in the education of young people, and the need to attach importance to the media and national values in their elimination. Also, there are social surveys aimed at ensuring that young people are interested in literature, reading and visiting theaters and museums.